CT contrast agent of Platinum nanodendrites: Preliminary study. (June 2019) - Khairil Anuar, MA; Harun, AZ; Abdul Razak, K; Rahman, WN
Abstract: Platinum nanodendrites (PtNDs) are high-Z nanomaterials (Z=78) that possess a promising potential to be introduced as a novel contrast agent in diagnostic radiology. The objective of this study is to investigate the performance of PtNDs as contrast agent in computed tomography in term of CT number and CNR. PtNDs of different sizes (29, 36, 42, 52 nm) were prepared into final concentration of 1.0 mM in 3 mL syringes. CT scans were performed on PtND samples, distilled water and iodinated contrast agent arranged in phantom. The scans of each samples were conducted at 0.6 mm slice thickness and 80 kVp setting. CT number and contrast to noise ratio (CNR) were measured and calculated. The attenuation property of PtNDs shows size dependent characteristics, as the smallest PtNDs tested (29 nm) shows the lowest CT number (3.73 ± 0.37), followed by 36 nm PtNDs (21.23 ± 0.77), 42 nm (62.77 ± 2.08) and 52 nm (89.33 ± 4.60). CNR quantification reveals that there are no significant different of CNR values for PtNDs of size 29 nm, 36 nm, and 42 nm (around 24.67 ± 0.25), while 52 nm PtNDs sees drop of CNR (20.14 ± 0.57). Compared to iodinated contrast agent, 42 and 52 nm PtNDs show higher CT number, with slightly reduced CNR. This preliminary study suggests that PtNDs have the potential to be applied as contrast agents for CT imaging. The study also demonstrates that the performance of nanomaterial based contrast agent and x-ray attenuation properties are dependent on nanoparticles size and further study is required to elucidate multiparameter involved.